Facile synthesis of tunable dendritic fibrous SBA-15 (DFSBA-15) with radial wrinkle structure - Chong, Chi Cheng; Syahida Nasuha, Bukhari; Cheng, Yoke Wang; Herma Dina, Setiabudi; Teh, Lee Peng; Aishah, Abdul Jalil (Elsevier Ltd, 2020)
In this study, typical mesoporous hexagonal rod-typed SBA-15 was successfully transformed into spherical shape with additional dendrimers, namely Dendritic Fibrous SBA-15 (DFSBA-15) by employing microwave-assisted microemulsion system. Physiochemical properties of DFSBA-15 were greatly influenced by aging temperature, urea/TEOS ratio, co-surfactant types, and aging time. It was found that the co-surfactant types were insignificant in controlling the pore size, while the aging conditions (temperature and time) were significant in controlling the fiber density. The analysis results (XRD, N2 physisorption, FTIR, and TEM) confirmed the optimal conditions for DFSBA-15 synthesis were at aging temperature of 100 °C, urea/TEOS ratio of 0.5, n-butanol as co-surfactant, and aging time of 12 h. The as-synthesized optimized DFSBA-15 was compared with the conventional SBA-15 via XRD, N2 physisorption, FTIR, CO2-TPD, NH3-TPD, TGA, TEM, and FESEM-EDX. As compared, DFSBA-15 rendered vast accessibility to the adsorption sites, higher basicity (≈86% enhancement) and acidity (≈66% enhancement), abundant siliceous framework and higher thermal stability (≈19% enhancement), owing to its radially oriented pores which elongated to the outer surface from the nucleus of its sphere. The outcome of this study anticipated the wide applications of DFSBA-15 in catalysis and biomedical fields by revealing the facile protocols of optimal DFSBA-15 synthesis.